2-Hydroxy-4-n-Propoxy Butyrophenone Oxime as an Analytical Reagent for Copper - Desai, G.R.; Desai, K.K (Asian Journal of Chemistry, 2012)
In the present work, the authors describe 2-hydrocxy-4-n-propoxy butyrophenone oxime as a gravimetric and photometric regent for copper.